EFFECT OF LIQUID CHLOROPHYLL FROM ALFALFA LEAVES (Medicago sativa l) AS A SUPPORTIF SUPPLEMENT TO THE PERFORMANCE OF BROILER CHICKENS - Ela Zabeta Ningrum; Lalu Faisal Fajri; Dina Oktaviana (Bantara Journal of Animal Science, 2019)
The purpose of this research is to determine the effect of liquid chlorophyll 8 ml can affect the weight, weight of cut, and carcass weight applied by broiler breeders in West Nusa Tenggara provision, especially Lombok. The type of the research that conducted in this research is laboratory experimental research with Randomized Post Test Design Only Control Group Design. This research uses a complete randomized design (RAL) with 4 kinds of treatment are arranged in random. The research used 24 samples of 1 day old chickens (DOC) maintained for 35 days, Liquid chlorophyll was administered through drinking water. The results of this research is using ANOVA variety using SPSS for windows 17 uji duncan stated that P0 was significantly different from P1, P2 and P3 in the weight test Body, cutting weight and carcass weight.